Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.

I got c=a-b+d

and c=a/b*d

can I use any other formulas?!!

Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.

I got c=a-b+d

and c=a/b*d

can I use any other formulas?!!

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.

I got c=a-b+d

and c=a/b*d

can I use any other formulas?!!

How did you get c=a/(bd)?? Why do you need other formulas? What was the original question they asked you?Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.

I got c=a-b+d

and c=a/b*d